2005
DOI: 10.2337/diacare.28.5.1175
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Deficiency Is Associated With Insulin Resistance in Obese Children

Abstract: OBJECTIVE -Magnesium deficiency has been associated with insulin resistance (IR) and increased risk for type 2 diabetes in adults. This study was designed to determine whether obese children exhibit serum or dietary magnesium deficiency and its potential association with IR.RESEARCH DESIGN AND METHODS -We studied 24 obese nondiabetic children (BMI Ն85th percentile) and 24 sex-and puberty-matched lean control subjects (BMI Ͻ85th percentile). We measured serum magnesium, indexes of insulin sensitivity, dietary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(122 citation statements)
references
References 39 publications
6
111
2
3
Order By: Relevance
“…In adults, higher intake is associated with an inverse risk of type 2 diabetes (66) and metabolic syndrome (67) . One of the few studies conducted in children suggested that magnesium deficiency is associated with insulin resistance in obese children (68) . Adolescents appear at greatest risk for low magnesium intake (64) .…”
Section: Discussionmentioning
confidence: 99%
“…In adults, higher intake is associated with an inverse risk of type 2 diabetes (66) and metabolic syndrome (67) . One of the few studies conducted in children suggested that magnesium deficiency is associated with insulin resistance in obese children (68) . Adolescents appear at greatest risk for low magnesium intake (64) .…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] While frank hypomagnesemia (serum level less than 0.61 mmol/L) usually occurs only in patients with uncontrolled diabetes, patients with magnesium concentrations less than 0.75 mmol/L may have preclinical disease. 15 …”
Section: Serum Magnesium Levels In Patients With Diabetes and Insulinmentioning
confidence: 99%
“…Hypomagnesemia could have been accounted for by the renal wastage (excessive excretion) seen in diabetes (Phuong-Chi et al, 2007) or part of the course of the disease state since magnesium is a trace element reportedly involved in glucose homeostasis (Resnick et al, 1993). It is also important to note that magnesium deficiency has been associated with insulin resistance (Huerta et al, 2005). It is also important to note that aside analytical methodology, Nwegbu et al 059 On comparing the means using t-test, there was no significant difference in the groups as p> 0.05 On comparing the means using t-test, there was no significant difference in the groups as p> 0.05 factors such as race, lifestyle and geographical influence have also been shown to influence outcomes of findings involving chromium (Yerlikaya et al, 2013).…”
Section: Discussionmentioning
confidence: 99%